Origin of phonon-limited mobility in two-dimensional metal dichalcogenides. (27th October 2021) - Chang, Hao; Wang, Hao; Song, Ke-Ke; Zhong, Min; Shi, Li-Bin; Qian, Ping
Abstract: Metal dichalcogenides are novel two-dimensional (2D) semiconductors after the discovery of graphene. In this article, phonon-limited mobility for six kinds of 2D semiconductors with the composition of MX2 is reviewed, in which M (Cr, Mo and W) is the transition metal, and X (S and Se) is the chalcogen element. The review is divided into three parts. In the first part, we briefly introduce the calculation method of mobility, including the empirical model and Boltzmann transport theory (BTE). The application scope, merits and limitations of these methods are summarized. In the second part, we explore empirical models to calculate the mobility of MX2, including longitudinal acoustic phonon, optical phonon (OP) and polar optical phonon (POP) models. The contribution of multi-valley to mobility is reviewed in the calculation. The differences between static and high-frequency dielectric constants (Δ ϵ ) are only 0.13 and 0.03 for MoS2 and WS2 . Such a low value indicates that the polarization hardly changes in the external field. So, their mobility is not determined by POP, but by deformation potential models. Different from GaAs, POP scattering plays a decisive role in its mobility. Our investigations also reveal that the scattering from POP cannot be ignored in CrSe2, MoSe2 and WSe2 . In the third parts, we investigate the mobility of MX2 using electron–phonon coupling matrix element, which is based on BTE from the framework of a many-body quantum-field theory. Valence band splitting of MoS2 and WS2 is induced by spin–orbit coupling effect, which leads to the increase of hole mobility. In particular, we review in detail the theoretical and experimental results of MoS2 mobility in recent ten years, and its mobility is also compared with other materials to deepen the understanding.